Risk Factors of Recurrent Wheeze in Infancy (Bangladesh Journal of Child Health, 2017)
Background: Recurrent wheeze in infancy is a common clinical problem and one of the most important causes of health facility visits in Bangladesh. Recurrent wheeze is an important manifestation of bronchiolitis, pneumonia and asthma.Objectives: The study was conducted to identify the risk factors associated with recurrent wheeze in infancy.Methods: This case control study was conducted at Dhaka Shishu Hospital and Dhaka Medical College Hospital (DMCH) during August 2008- June 2009 including 50 infants (1- 12 months of age) with recurrent (3 or more) wheeze or wheeze persisting for more than one month during first year of life as study group and 50 children (12 months to 24 months of age) who had no wheeze during first year of life as control groupResults: The study group comprised of 34 (68.0%) male and 16(32.0%) female infants and control group included 31(62.0%) male and 19 (38.0 %) female children. The mean age of study group was 9 months and that of the control group was 18 months. The median age of first attack of wheeze was 4 months. Twenty one (42.0%) infants in study group and 29 (58.0%) in control group were exclusively breastfed. On the other hand, 29 (58.0%) studied cases and 21(42.0%) controls were mixed fed (formula, cows milk, suji along with breast milk).The study children who were exclusively breastfed had lesser incidence of recurrent wheeze than those who were mixed fed but the difference was not significant (P> 0.05). There was past history of bronchiolitis in 45 (90.0%) cases of study group in comparison to only 3 (6.0%) cases of control group (p